A Golgi and tonoplast localized S-acyl transferase is involved in cell expansion, cell division, vascular patterning and fertility in Arabidopsis - Qi, Baoxiu (The New phytologist, 2013)
© 2013 The Authors. New Phytologist © 2013 New Phytologist Trust.